THE MEANING OF RELIGIOUS VEILING IN POST-SOVIET KAZAKHSTAN. - Tynysbekova, Yelnura (Nazarbayev University School of Sciences and Humanities, 2024)
Following the collapse of the Soviet Union, citizens in former Soviet Republics embarked on a profound "quest for identity," leading to the emergence of various religious and political groups, particularly in Central Asian states. Since the 1990s, there has been a noticeable rise of Islamic groups and an overall Islamization of society in these regions, characterized by an increase in veiled women, bearded men, mosques, and madrasas. The phenomenon of the quest for identity in former Soviet Central Asian Republics to an extent followed the flow of a broader revival of religion witnessed in Muslim-majority states like Turkey, Egypt, and Iran. The focus of this capstone project is to explore and elucidate the significance of veiling among women in post-Soviet Kazakhstan, examining the reasons behind veiling, societal and state responses, and the diverging interpretations between state agendas and individual meanings attributed to veiling. This discrepancy sheds light on the complex interplay between state policies, cultural practices, and personal interpretations of veiling.
Keywords: Type of access: Open access; veiling; Post-Soviet Kazakhstan